Synthesis of Substituted Fluorenes by Cascade Allenylation, Electrocyclization and Intramolecular Friedel–Crafts Reaction of 1,3-Diene-Substituted Propargylic Alcohols - Xu, Xiangsheng; Li, Tao; Li, Xiaoqing; Shao, Jiangbin (Synlett, 2013)
A concise, one-step synthesis of substituted fluorenes through TiCl4-promoted cascade allenylation, electrocyclization and intramolecular Friedel–Crafts reaction of 1,3-diene-substituted propargylic alcohols has been developed. An interesting substituent-dependent regioselectivity was observed.
Keywords: allenylation; electrocyclization; intramolecular reactions; Friedel–Crafts; 1,3-dienes; fluorenes